Removal dyes textile effluent applying advanced technology - Bermeo Garay, Martha (2016)
At present an environmental problem are refractory organic compounds such as dyes, which interfere with photosynthetic processes carried out by organisms in water bodies. Contaminants present in wastewater from industries such as textiles, paper, and pharmaceutical tannery among others, whose processes generate large volumes. The objective of this research was to remove dyes synthetic effluent textile, applying advanced technology to which electrocoagulation is used, this research allows to carry out a treatment without reagents, using electrical charges which destabilize the colloidal particles facilitating their precipitation, for which iron electrodes used with 0,8 mm spacing. The methodology is based on variations in current density, pH and residence time, the response variables are percentage of color removal and chemical oxygen demand. As a result of the experimentations removal efficiency of 97,57% of Chemical oxygen demand color and 99,11% , current density 27,92 A / m2, pH 10 and a reaction time of 8min was obtained. This experience can be applied to other effluents.